Ubiquitination and SUMOylation in HIV Infection: Friends and Foes - Colomer-Lluch, Marta (Curr Issues Mol Biol, 2019)
As intracellular parasites, viruses hijack the cellular machinery to facilitate their replication and spread. This includes favouring the expression of their viral genes over host genes, appropriation of cellular molecules, and manipulation of signalling pathways, including the post-translational machinery. HIV, the causative agent of AIDS, is notorious for using post-translational modifications to generate infectious particles. Here, we discuss the mechanisms by which HIV usurps the ubiquitin and SUMO pathways to modify both viral and host factors to achieve a productive infection, and also how the host innate sensing system uses these post-translational modifications to hinder HIV replication.